2020
DOI: 10.3390/nu12041190
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferide Enhances Chemosensitivity of Human Lung Adenocarcinoma A549 Cells Mediated by the Decrease in Phosphorylation of Akt and Claudin-2 Expression

Abstract: Claudins (CLDNs) play crucial roles in the formation of tight junctions. We have reported that abnormal expression of CLDN2 confers chemoresistance in the spheroids of human lung adenocarcinoma A549 cells. A food composition, which can reduce CLDN2 expression, may function to prevent the malignant progression. Here, we found that ethanol extract of Brazilian green propolis (EBGP) and kaempferide, a major component of EBGP, decrease CLDN2 expression. In the two-dimensional culture model, EBGP decreased the tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The tight junctional localizations of CLDN1, CLDN2, and ZO-1 were examined by immunocytochemistry, as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tight junctional localizations of CLDN1, CLDN2, and ZO-1 were examined by immunocytochemistry, as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, CLDN2 may be a novel target for the development of anticancer drugs. Some flavonoids, including kaempferol, luteolin [ 19 ], quercetin [ 20 ], and kaempferide [ 21 ], can reduce the expression level of CLDN2 in A549 cells. The transcriptional activity of CLDN2 is up-regulated by the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) and mitogen-activated protein kinase (MEK)/extracellular signal regulated kinase (ERK) pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, guanosine also has excellent antitumor activity and significant inhibitory activity on lung adenocarcinoma A5449 cell line [ 43 ]. Kaempferol and quercetin are the most widely studied antitumor substances; it has been reported that Kaempferol can reduce the expression of CLDN2 in A549 cells and further inhibit cell proliferation and migration [ 44 ]. It has been demonstrated that the anticancer activity of quercetin is facilitated via the activation of the adenosine monophosphate (AMP)-activated protein kinase (AMPK) pathway, suppression of the phosphoinositide 3-kinase/PI3K/AKT/mammalian target of rapamycin/NF- κ B pathway, upregulation of p53 activation, and the apoptosis pathway, and when used with other chemotherapeutic agents, quercetin can achieve tumor-improving results by enhancing apoptosis and reducing side effects [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 84 potential targets were obtained by taking the intersection. The majority of the compounds were flavonoids, such as quercetin, luteolin, kaempferide, and kaempferol, which have long been reported to have significant antitumor activity [ 33 36 ]. In this research, only eight compounds were found to meet the requirements of OB ≥30% and DL ≥ 0.18.…”
Section: Discussionmentioning
confidence: 99%